Emotional Focus Coping on Early Childhood Marriage Actors in Selayar - Andi Pramesti Ningsih (Journal of Public Health and Pharmacy, 2023)
This study aims to reveal emotional focus coping performed by early marriage couples in Selayar. This research is a qualitative research with a phenomenological approach. The data were obtained by means of in-depth interviews and focus group discussions with 12 informants consisting of teenagers who married at an early age, parents, health workers and family planning instructors. Domain analysis is used to identify semantic relationships in the data found. The results showed that in addition to emotional focus coping, the informants also used problem focus coping in undergoing early marriage. The forms of coping with emotional focus found were self-controlling, escape-avoidance, and positive appraisal. Therefore, counseling is needed for adolescents who marry at an early age.